Aeronautical Periodicals (1783–1945) – A Reflection of Air Power - Sollinger, Guenther (History of Engineering Sciences and Institutions of Higher Education, 2019)
Periodical publications have played an important role in the development of aeronautics, providing a platform for scientific exchange and informing the public about the ongoing progress. This study analyzes periodicals covering the issues related to aeronautics from 1783 to 1945 on a worldwide scale. It assumes that the number and diversification of periodicals dedicated to aeronautics published in a given country depend directly on the level of development of air power in that country. The result shows that periodicals from only four countries dominated, three fourths of all titles published coming from France, Germany, Great Britain and the United States. In 1945, by the end of the period under study, these four countries, together with the Soviet Union and Japan, were also the world’s dominant air powers in terms of both civil and military air activities. The study also analyzes the development of periodicals over time, the diversification of periodicals by major subject areas and the interdependence of information flows between the four major air powers.